The Characteristics of Heritage Stations and Its Transformation along the Railway Track of Jombang City to Tuban - Pungki Indriatmiko; Ikaputra (Department of Architecture and Planning, Faculty of Engineering, Universitas Gadjah Mada, 2021)
The station is one mode of transportation that shows the progress of the civilization of a city. Stations in Indonesia are one of the modes of transportation that are influenced by the development of transportation technology problems that began in 1983 and is one of the third train developments in the world. This study wanted to find out about the facade characteristics possessed by station-stations in Indonesia. In this study, it is intended to see the characteristics formed from the building facades, the proportions resulting from the composition of the existing space which will be reflected in the proportions and scale of the building. The station building on the Jombang Kota - Tuban track has the characteristics of a long building with the facade composition from the direction of passenger arrival dominated by the composition of the windows and on the reverse side the composition of the doors. Station buildings have a gate which is always at the end of the station building. The entrance gate of the building represents the convenience for passengers to enter with an opening that is wide enough and easily recognizable.